Persepsi Guru PJOK dan Guru Kelas terhadap Peran PJOK dalam meningkatkan Kesejahteraan Emosional Siswa - Reja Firman Saputra; Diana Santi; Rizva Alvina; Siti Nabilah Hasna; Ayu Rahmawati; Rizky Nurul Melyani; Mutiara Harkit Kamilatul Pu’adah; Rahmat Permana (Lembaga Pengembangan Kinerja Dosen, 2025)
The purpose of this article is to describe the perceptions of physical education teachers and class teachers towards the role of physical education in improving the emotional well-being of elementary school students. The main focus of the discussion is how PJOK lessons not only have an impact on physical development, but also support students' emotional growth, self-confidence, discipline, and social interaction. The methods used in this paper are observation and descriptive qualitative interviews with three resource persons, namely two physical education teachers, one class teacher at SDN 5 Imbanagara Raya. Data was collected through direct question and answer sessions that explore their experiences and views in observing changes in student behavior through PJOK activities. Based on the results of the interview, it was found that PJOK has an important role as a medium for student expression, especially for those who tend to be quiet or lack confidence. Physical activities and team games help students in forming self-confidence, discipline, and cooperation skills. In addition, collaboration between class teachers and physical education teachers is also an important key in adjusting teaching approaches that are responsive to students' emotional conditions. Thus, physical education contributes significantly to creating a learning environment that supports students' mental and emotional health.